Passive localization of a forklift based on a template matching position tracking algorithm - Ebad Zahir; Manukid Parnichkun (International Journal of Advanced Robotic Systems)
The presented research investigates the accuracy of a localization algorithm using lidar (NAV-350) pose data in a GPS denied environment. A template matching solution is presented using the corners of the workspace area as markers. Results are also compared against the lidar NAV-350's own software solution which are based on average reflector distance. The presented algorithm has shown to have a higher accuracy in most cases. Data is analyzed for approximately 100 different locations in a workspace of 8.9 m by 10.7 m using an industry standard forklift with a base dimension of 1 m × 1.3 m. This paper shows how the algorithm can successfully determine the x , y coordinates and heading angle of the forklift in real time.